Atmospheric Plasma surface treatment of Styrene-Butadiene Rubber - Carreira, Cátia A.; Silva, Ricardo; Pinto, Vera V.; Ferreira, Maria José; Sousa, Fernando; Silva, Fernando; Pereira, Carlos M. (International Conference on Plasma Surface Engineering, 2013)
Thermoplastic rubbers are widely used in a large number of applications (e.g. footwear, adhesives manufacturing, molded or extruded goods). Due to the non-polar nature of these rubbers, poor adhesion is achieved with polar polyurethane (PU) adhesive thus, a surface treatment is required to chemically modify the rubber surface and produce suitable joints. Surface treatments have been demonstrated to be suitable for the improvement of adhesion and wettability properties of non-polar synthetic rubbers. Over the last two decades progresses in adhesion of rubber were achieved by changing of the ingredients in rubber composition or by modifying surfaces by the use of a chemical agent (halogenation, cyclization, etc.) or using high energy irradiation such as bombarding the surface by electron beam or gamma irradiation. Actually, wet-chemical treatments are not well acceptable because of environmental and safety considerations and question on uniformity and reproducibility. Plasma surface treatment process was been proposed as an environmentally friendly and have gained large acceptance because it can be easily integrated into existing production lines and because their effectiveness in the treatment of several materials with different shapes and sizes. The effectiveness of plasma treatment on enhancement of adhesion depends on the gas used to generate the plasma and also on the formulation of the rubber. Vulcanized rubbers like, styrene-butadiene rubber (SBR), are especially difficult to bond due to low molecular weight ingredients in their formulation that may migrate to the rubber surface limiting its interaction with the adhesive. This study attempts to find an alternative treatment to improve the adhesion of SBR surface and PU adhesive. Plasma treatments were performed in an air plasma system from Acxys and were selected three types of SBR rubbers with different percentages of styrene-butadiene which were provided by Procalçado. The effect of experimental variables such as distance, speed and scan number on the adhesion of PU adhesive was evaluated and compared with halogenated SBR rubbers.